2016
DOI: 10.1111/jep.12660
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for guideline adherence in knee osteoarthritis care: A qualitative study from the patients' perspective

Abstract: Rationale, aims and objectives Guidelines for patients with knee osteoarthritis (OA) are suboptimally implemented in clinical care. To improve guideline adherence, patients' perceived barriers and facilitators in current care were investigated.Methods Eleven patients with knee OA were extensively interviewed using a semistructured script based on quality indicators. Directed content analysis, within the framework of Grol and Wensing, was performed to describe barriers and facilitators in 6 domains: guideline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…This is consistent with studies of people with OA which found that some people have fears that exercise is damaging to their joints 50 or will worsen pain. 51 Overcoming misconceptions about OA may require more emphasis on public education that highlights the early signs and symptoms, de-emphasises the need for X-ray findings to diagnose early OA, challenges the assumption that all OA is inevitably progressive and explains the benefits of exercise. Effective, collaborative patient-provider communication about OA management is also crucial.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with studies of people with OA which found that some people have fears that exercise is damaging to their joints 50 or will worsen pain. 51 Overcoming misconceptions about OA may require more emphasis on public education that highlights the early signs and symptoms, de-emphasises the need for X-ray findings to diagnose early OA, challenges the assumption that all OA is inevitably progressive and explains the benefits of exercise. Effective, collaborative patient-provider communication about OA management is also crucial.…”
Section: Discussionmentioning
confidence: 99%
“…From the patient perspective, a qualitative study of patients with osteoarthritis of the knee [32] found that poor comprehension of the disease process, negative experiences with drug therapies, poor communication by the health professional and disagreement with the recommendations of guidelines, presented key barriers to adherence. Within those disagreements an insistence on medical imaging and a fear that physiotherapy aggravates pain were important issues.…”
Section: The Challenge Of Implementationmentioning
confidence: 99%
“…We can divide barriers to adhering to OA treatment guidelines into four themes: “OA is not that serious,” reflecting an attitude that everybody eventually gets OA as they grow older, “Clinicians are, or perceive they are, under-prepared,” “Personal beliefs at odds with providing recommended practice,”, and “Dissonant patient expectations” [ 11 ]. Factors that facilitate improved adherence to the guidelines are patient-tailored strategies to improve patients’ knowledge, self-management, and communication with healthcare professionals on matters such as shared decision making [ 12 ]. To overcome the discrepancy between the guidelines and practice, a nationwide program titled “Better management of patients with osteoarthritis” (BOA) was initiated in Sweden in 2008 to offer information and individually adapted exercise to all patients with hip and knee OA, in accordance to guidelines for OA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%